2021
DOI: 10.1016/j.tranon.2021.101202
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization synergizes with oxaliplatin in lung cancer immunotherapy via enhanced tumor cell phagocytosis

Abstract: Highlight LLC cells pretreated with OXA were more prone to be phagocytized by M1 than M2 macrophages. M2 repolarized to M1 by R848 in vitro showed enhanced phagocytic ability to OXA-treated LLC cells. Macrophage polarization from pro-tumor M2 to anti-tumor M1 synergizes with OXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Treatment with R848 is effective in various types of cancer, such as breast, pancreatic, and colorectal cancer [ 112 , 115 , 116 ]. Moreover, recent studies focusing on macrophages have highlighted the therapeutic efficacy of R848, either alone or in combination with other drugs, in lung cancer [ 117 , 118 ].…”
Section: The Tlr7/8 Signaling Pathwaymentioning
confidence: 99%
“…Treatment with R848 is effective in various types of cancer, such as breast, pancreatic, and colorectal cancer [ 112 , 115 , 116 ]. Moreover, recent studies focusing on macrophages have highlighted the therapeutic efficacy of R848, either alone or in combination with other drugs, in lung cancer [ 117 , 118 ].…”
Section: The Tlr7/8 Signaling Pathwaymentioning
confidence: 99%
“…On the other hand, several studies have reported that the M2-polarized TAMs contribute to the OXA resistance by suppressing the cancer cell apoptosis (Fu et al, 2019 ; Guo et al, 2017 ; Lan et al, 2021 ). As expected, OXA has demonstrated synergy with R848, a small molecule that converts macrophages from M2 to M1, in cancer treatments (Li et al, 2021 ; Liu et al, 2020 ). Our results showed that the Oxa+ E. coli co-treatment robustly re-polarized the TAMs into the M1 subtype.…”
Section: Discussionmentioning
confidence: 54%
“…39 R848 is a potent TLR7/8 agonist that can shift the polarization of TAMs towards the M1 phenotype. 40 Similarly, in IL-4 induced M2 polarized J774.A macrophages, mLAPMi-R848 significantly increased the CD80 marker, indicating that macrophages were polarized to M1 inflammatory macrophages (Fig. S10 †).…”
Section: Paper Biomaterials Sciencementioning
confidence: 84%